Deep Learning for Computer Vision : Expert techniques to train advanced neural networks using TensorFlow and Keras. - Shanmugamani, rajalingappaa (Packt Publishing, 2018)
Deep learning has shown its power in several application areas of Artificial Intelligence, especially in Computer Vision, the science of manipulating and processing images. In this book, you will learn different techniques in deep learning to accomplish tasks related to object classification, object detection, image segmentation, captioning ...